CATEGORIES OF «POLITENESS» IN SPEECH ACTS OF UTTERING «REFUSALS», «DENIALS» AND «SURPRISES» IN RUSSIAN AND AMERICAN CULTURES (Scientific journal of the Fergana State University, 2024)
This article is dedicated to the study of politeness categories in speech acts of «refusals», «denials», and «expressions of surprise» in Russian and American cultures. It analyzes the differences and similarities in the manifestation of politeness when Russian and English speakers interact. The paper examines examples from everyday communication that reveal cultural features of politeness expression in situations requiring refusals, denials, or expressions of surprise. Special attention is given to the strategic and tactical methods used to mitigate the negative effect of refusals and denials, as well as culturally conditioned reactions to surprise. The research results show that politeness in these speech acts is highly dependent on cultural context and traditions, necessitating the consideration of intercultural differences for successful communication. The article contributes to the development of politeness theory and may be useful for specialists in intercultural communication, linguistics, and sociolinguistics.